Search for the decay D0→π+π−μ+μ− - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; et al. (Physics letters, 2014)
A search for the D0→π+π−μ+μ− decay, where the muon pair does not originate from a resonance, is performed using proton-proton collision data corresponding to an integrated luminosity of 1.0fb−1 recorded by the LHCb experiment at a centre-of-mass energy of 7 TeV. No signal is observed and an upper limit on the relative branching fraction with respect to the resonant decay mode D0→π+π−ϕ(→μ+μ−), under the assumption of a phase-space model, is found to beB(D0→π+π−μ+μ−)/B(D0→π+π−ϕ(→μ+μ−))<0.96 at 90% confidence level. The upper limit on the absolute branching fraction is evaluated to be B(D0→π+π−μ+μ−)<5.5×10−7 at 90% confidence level. This is the most stringent to date.